The Relationship between Student Learning Interest and Learning Outcomes - Anang Saiful Wahdi; Agus Effendi; Wiji Khurniawati (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2024)
Student learning outcomes are a crucial achievement in learning, because learning outcomes can be a measure of student ability and also the success of learning from a teacher. Related to maximum learning outcomes, one of the factors that influence it is interest. In learning activities, if students have an interest in learning, they will feel that learning is very important so that they try to focus their attention on things related to learning activities and happily do it without any coercion from anyone. The purpose of this study is to find out, Does student interest in learning have a continuous relationship with learning outcomes? What are the factors that influence students' interest in learning? And, How to increase students' interest in learning? This research uses qualitative research. The population in this study were class X PPLG B students at one of the State Vocational Schools in Surakarta, totalling 36 students. The research variables are learning interest and learning outcomes. The data collection technique of learning interest uses observation in teaching assistance & guided learning practice while learning outcomes data from summative assessment at the end of learning & student projects. Keywords: Learning outcomes, Learning interest, Students, Vocational school